The Role of Trust in Moderating the Impact of Affiliate and Social Media Marketing on Financial Service Purchase Decisions - Yugita, Tesa Uci; Kasmo, Arief Bowo Prayoga (Formosa Journal of Applied Sciences, 2024)
This study aims to evaluate the impact of affiliate marketing, social media marketing, brand image, and service quality on purchasing decisions for financial services, with trust acting as a moderating variable to enhance these purchase decisions, particularly in the context of credit fund distribution. A sample of 324 respondents from across Indonesia was analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that affiliate marketing and social media marketing both have significant positive effects on purchasing decisions for financial services. Additionally, brand image also significantly and positively influences purchasing decisions. Contrary to expectations, service quality does not show a significant positive impact on purchasing decisions. Crucially, trust is identified as a key moderating factor, particularly enhancing the relationship between brand image and purchase decisions.